Knowledge and identification of pediatric palliative care needs at a specialized institute in Peru - Argume Huaylinos, Angela Debora (2024)
Objective: To determine the relationship between knowledge and identification of palliative care (PC) needs among medical specialists at the Instituto Nacional de Salud del Niño (INSN - National Institute of Child Health) in Breña, Lima, Peru, in July 2023. Materials and methods: A cross-sectional, analytical and observational study was conducted. Results: The study included 180 medical specialists, with 34.40 % aged between 30 and 39 years and 51.00 % being women. The majority had a medical specialty (pediatrics), with intensive care medicine being the most frequent subspecialty. Only 12.00 % of the participants had received prior PC training. The average global PC knowledge score was 11.65 ± 2.83. Qualitatively, most participants rated their knowledge as intermediate and demonstrated an adequate level of identification of pediatric palliative care (PPC) needs. The average score in the questionnaire for identifying patients with PPC needs was 3.53 ± 0.93. All participants with prior PPC training showed adequate identification of PPC needs. The global knowledge score was higher among those who adequately identified PPC needs compared to those who did not (median 12 [IQR: 10–14] vs. median 11 [IQR: 8–2]; p: 0.0068). Likewise, the theoretical and legal domain scores were higher in those with adequate identification of PPC needs. Conclusions: Most participants rated their knowledge at an intermediate level, with ethics scoring the lowest among domains. The majority demonstrated an adequate ability to identify PPC needs. A significant but weak correlation was found between the global PC knowledge score and the identification of PPC needs, as well as between the legal domain and the identification of PPC needs. These findings support the implementation of PPC training programs for medical specialists focusing on both theoretical knowledge and practical skills.